The Relationship Between Work Engagement and Burnout in Ditpolair Korpolairud Baharkam Polri - Rizky Mukti Aryatno (Psychological Research and Intervention, 2019)
The aim of this study was to investigate the relationship between work engagement and burnout in Korpolairud Ditpolair Baharkam Polri. This study was a correlational study with quantitative method. 120 members of Korpolairud who worked in the Subditpatrolair division were involved as participants. Simple random sampling was used as  sampling method and 4 point Likert scale as data collection techniques. The work engagement scale was based on Schaufeli’s theory with aspects namely vigor, dedication, and absorption. Menawhile, the burnout scale was based on Maslach’s theory with aspects namely emotional exhaustion, depersonalization, and personal accomplishment. Based on data analysis using Pearson Product-Moment correlation test, the results of this study showed that there was a correlation between work engagement and burnout in Korpolairud Ditpolair Baharkam Polri as proved by -0.752 coefficient value and p=0.00. It can be concluded that the correlation between work engagement and burnout was significant and negatively correlated.